PENGARUH TUTUPAN LAHAN TERHADAP FENOMENA URBAN HEAT ISLAND DI KOTA SEMARANG - Rizal Mubarok; Bintang Septiarani; Reny Yesiana; Pangi Pangi (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2021)
Semarang is the capital city of Central Java Province which is a metropolitan city that is located in the north of Java Island. Semarang City had a population of 1,249,230 people in 1990 and increased to 1,653,524 people in 2020 or 32.4%. As for residential area in 1990 it was 12,355 Ha and in 2020 it was 17,070 Ha or 38.2%. The data shows that population growth in Semarang City is directly proportional to the area of land cover, especially residential area. This study aims to determine the effect of land cover on the urban heat island (UHI) phenomenon in Semarang City. The research method used in this research is land cover analysis (supervised classification), Normalized Difference Vegetation Index (NDVI), Land Surface Temperature (LST), overlay, and descriptive analysis. This method is used to obtain data on land cover, temperature, and the effect of land cover on the urban heat island. Based on the results of the analysis, it is known that the city of Semarang has a significant land change from vegetation land to residential land. Vegetation land in 1989 was 27,055 Ha, changed to 16,316.4 Ha in 2020. The area of residential land and built-up land changed from 6,349.2 Ha in 1989 to 18,015.4 Ha in 2020. The temperature classification in Semarang City is dominated by by class III, which is 260 -300 Celsius. The temperature area in class I decreases and in class V increases. In built-up land and settlements, class III temperature has a land area value of 7.9 Ha in 2020, while in 1989, 1999, and 2009 it has an area of less than 2 Ha. Based on the studies that have been carried out, it can be concluded that changes in land cover in Semarang City, especially from vegetation to settlements, also cause changes in temperature which cause the UHI phenomenon in Semarang City.